Ketamin als Anästhetikum bei der Elektrokrampftherapie = Ketamine as anesthetic agent in electroconvulsion therapy - Janke, Christoph; Thiel, Manfred; Sartorius, Alexander (Der Anaesthesist, 2015)
Background: Electroconvulsive therapy (ECT) is a well-established, safe and effective treatment for severe psychiatric disorders. Ketamine is known as a core medication in anesthesiology and has recently gained interest in ECT practice as there are three potential advantages: (1) ketamine has no anticonvulsive actions, (2) according to recent studies ketamine could possess a unique intrinsic antidepressive potential and (3) ketamine may exhibit neuroprotective properties, which again might reduce the risk of cognitive side effects associated with ECT. Objectives: The use of ketamine in psychiatric patients has been controversially discussed due to its dose-dependent psychotropic and psychotomimetic effects. This study was carried out to test if the occurrence of side effects is comparable and if seizure quality is better with ketamine when compared to thiopental. Material and methods: This retrospective study analyzed a total of 199 patients who received ketamine anesthesia for a total of 2178 ECT sessions. This cohort was compared to patients who were treated with thiopental for 1004 ECT sessions. Results and discussion: A repeated measurement multiple logistic regression analysis revealed significant advantages in the ketamine group for seizure concordance and postictal suppression (both are surrogates for central inhibition). S-ketamin also necessitated the use of a higher dose of urapidil and a higher maximum postictal heart frequency. Clinically relevant psychiatric side effects were rare in both groups. No psychiatric side effects occurred in the subgroup of patients with schizophrenia (ketamine: n = 30). The mean dose of S-ketamine used increased in the first years but stabilized at 63 mg per patient in 2014. From these experiences it can be concluded that S-ketamine can be recommended at least as a safe alternative to barbiturates.